Sistem Pendukung Keputusan Penilaian Kinerja Karyawan Menggunakan Metode TOPSIS - Adam Huda Nugraha (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Employee performance appraisal is an important stage in job evaluation in a company that can significantly improve the quality of work and ensure the continuity of company activities. This assessment process is based on a number of predetermined criteria, such as responsibility, cooperation, honesty, discipline, and communication. Each employee is assessed based on their ability to meet and exceed the quality standards set by the company. In this context, the use of the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method emerges as an effective approach. This method helps in identifying employees who are closest to the ideal solution and the extent to which they meet the predefined criteria. For example, TOPSIS can be used to determine the most responsible, most collaborative, or the most honest employee. Through systematic and objective employee performance appraisals, companies can measure and monitor employee progress, as well as provide constructive feedback for further development. This not only helps increase employee motivation and productivity, but also supports the achievement of overall company goals. By combining established quality standards with appropriate evaluation methods such as TOPSIS, companies can optimize the employee performance assessment process to support long-term growth and success. The calculation results show that Rere (A4) ranks first with the highest score of 0.764, indicating that she is the best alternative among the five candidates.